An Integrative Framework for Transforming Fiqh Learning in Pesantren: Turāth, Maqāṣid al-Sharīʿah, and Digital Pedagogy - Abdullah, Rusdi; Sahari, Sahari; Rahman, Abdul; Nuraini, Amalia; Hajriana, Hajriana (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
This study examines the transformation of fiqh learning in Islamic boarding schools using a qualitative approach with a multi-site case study design in three Islamic boarding schools, namely Al-Falah Banjarbaru (South Kalimantan), Hidayatullah Balikpapan (East Kalimantan), and Al-Bayan Makassar (South Sulawesi). Data were collected through in-depth interviews, participant observation, and document analysis with fiqh instructors, curriculum managers, and teachers in the three locations. The results of the study show five main findings, namely (1) the transformation of the learning paradigm from teacher-centered to student-centered has taken place with varying intensity in each Islamic boarding school; (2) the integration of turath and contemporary issues has become a shared awareness of teachers, but its implementation is still sporadic; (3) the digitalization of fiqh learning is still in its early stages; (4) the maqashidiorientation is implicitly embedded in the teachers' pedagogical vision; and (5) the bahtsul masāil model, legal case studies, and direct practice have the greatest potential as a bridge between tradition and innovation. This research formulates a learning transformation framework as an original conceptual model that integrates three pillars: turath as the epistemological basis, maqāṣid al-sharīʿah as a contextual analytical framework, and digital pedagogy as an adaptive learning strategy in a complementary and non-substitutive dialectical relationship. This framework offers a maqāṣid al-sharīʿah approach as an alternative to the traditionalism-modernism dichotomy in Islamic boarding school education and provides operational guidance for the development of a fiqh curriculum that is responsive to contemporary needs without sacrificing the authenticity of traditional knowledge.